NARRATOR’S XENOPHOBIA AS SEEN ON THE CALL OF CTHULU BY H.P LOVECRAFT: PSYCHOLOGICAL APPROACH - Muhammad Alif Faturrachman (eScience Humanity Journal, 2020)
This study titled Narrator Xenophobia as seen in The Call of Cthulu by H.P Lovecraft: A Psychological Approach is a psychoanalytical analysis of Howard Phillips Lovecraft’s The Call of Cthulu (1928), the study aimed to identify the personality of Francis Wayland Thurston, the main narrator of the story, xenophobia and self-defense mechanism issues and also figure out the characterization of this character. As a literary research, this study utilized the use of psychoanalytic criticism by Sigmund Freud as the analytical tool and also the concept of self-defense mechanism proposed by Berger. In addition, this study utilized the descriptive qualitative research method, where the writer read the short story thoroughly to obtain the data needed for the discussion. The finding of this research is that the character of Francis Wayland Thurston does has some issues with xenophobia which causes him to utilized the self-defense mechanism needed to ensure his safety. Therefore, the writer concluded that Francis Wayland Thurston in this short story does represent the characteristic of a xenophobic person.